Risk Factors of Smoking Among Health Care Professionals. (October 2014) - Shahbazi, Sara; Arif, Ahmed A.; Portwood, Sharon G.; Thompson, Michael E.
Background: Health care professionals (HCPs) play a vital role at various levels of smoking cessation programs to reduce tobacco use in general populations. However, their smoking habits may limit their ability to intervene with their patients who smoke.Aims: To determine prevalence rates of current smoking and examine sociodemographic and work-related factors associated with current smoking among HCPs.Methods: A statewide survey was conducted in a representative sample of 4 groups of HCPs, physicians, nurses, respiratory therapists, and occupational therapists, with active licenses in Texas in 2003. Weighted prevalence estimates of current smoking rates were computed. Survey logistic regression analysis was used to investigate associations between individual characteristics and current smoking.Results: There were 3600 HCPs included in the analysis. The overall prevalence of current smoking was 9% with the highest prevalence (16%) recorded among respiratory therapists and the lowest prevalence (3%) recorded among physicians. In the multivariable logistic regression analysis non-Hispanic white HCPs were almost 4 times as likely to be current smokers (adjusted odds ratio= 3.95, 95% confidence interval = 1.24-12.59) and those working for 50 hours or more per week were twice as likely to be current smokers (adjusted odds ratio = 2.07, 95% CI = 1.20-3.57). Compared with physicians, all other HCP groups had significantly greater odds of currently smoking. HCPs who were female and resided or worked in rural settings had higher smoking rates in univariable analysis only ( P < .05).Conclusions: Smoking is prevalent among certain HCP groups. Working long hours was identified as an important occupational factor associated with current smoking.